Gender Differences on Job Satisfaction of the Five-Star Hotel Employees: The Case of the Turkish Hotel Industry - Derya k, K.; Uysal, Muzaffer; Magnini, V. (Emerald Group Publishing Limited, 2012)
Purpose – The purpose of this research is to examine gender differences while controlling for select variables on job satisfaction using data collected from employees in the hospitality industry. Design/methodology/approach – The study was conducted on 397 employees (234 males and 163 females) in five-star hotels in Ankara, Turkey. Findings – The level of job satisfaction is determined by four factors: “management conditions”, “personal fulfillment”, “using ability in the job”, and “job conditions”. The study results show that significant gender differences exist with regard to the “using ability in the job” dimension of job satisfaction. After controlling such variables as age, marital status, monthly income level, education, type of department, position held, length of time in the organization, length of time in the tourism sector, and frequency of job change, most gender differences remained significant. Research limitations/implications – The use of hotel employees solely representing five-star hotels may be considered a limitation of this study. The results provide information that can be utilized in understanding, maintaining, and increasing the satisfaction levels of both female and male employees. The findings indicate that fairness and equity in salary and wages are effective tools to increase the job satisfaction levels of male and female employees. Originality/value – This study focuses on the identification of gender-specific drivers of job satisfaction while controlling for select demographic variables. The study provides insight into employees’ perceptions of certain aspects of the nature of the hospitality and tourism sector in Turkey.